Analisis Hukum Terhadap Pelaku Aborsi Menurut Hukum Pidana Yang Berlaku Di Indonesia - Adi Laksono; Mohamamad Rafi’e; Muhammad Chalil (CV. ITTC INDONESIA, 2023)
Human right, which are guaranteed by the 1945 Constitution Article 28 A, including the rightto life and the right to defend life, have become important over time. However, in everyday life, the norms and ethics that should be applied to minors are often ignored. This is very detrimental for children who are still vulnerable to promiscuity and adults acts such as rape or unlawful sexual relations. Regarding unwanted pregnancies, abortion or abortion provocateur is a serious problem. Although the law prohibits it, there are many cases whereminors or even doctors assist in this act. However, doctors who perform provocatus abortions must comply with medical recommendations permitted by law, as regulated in Article 60 paragraph (2) of Law Number 17 0f 2023 concerning Health. The thesis writer uses the statue Approach to research to legal issue. This approach involves an analysis of all laws and regulations realated to the legal issue. During the discussion, it was concluded that abortion provocation is a crime prohibited by law, both for minors and for doctors who help them.